Advanced-stage Endometrial Stromal Sarcoma Presenting as Primary Infertility in a Young Nulligravida: A Case Report - Ankita PATTANAIK; Jasmina BEGUM; Sweta SINGH; Deepthy BALAKRISHNAN; Suvradeep MITRA (Medeniyet Medical Journal)
Endometrial stromal sarcoma (ESS) rarely causes infertility in young women. We report a nulligravida in her 30s who presented with primary infertility of 15 years. Hysteroscopy revealed a submucosal necrotic fibroid polyp. Ultrasonography detected multiple intramural fibroids. Open myomectomy with polypectomy was performed. Histopathology revealed low-grade ESS (LGESS) within the fibroid polyp. Subsequently, the patient underwent completion surgery. Her final diagnosis was estrogen-receptor positive LGESS stage IIIB, and she was suggested anastrozole adjuvant therapy and long-term surveillance. ESS with abnormal perimenopausal bleeding, though the most common presentation, may not always observed. Hence, a high index of suspicion of ESS should always be kept as a differential diagnosis in uterine fibroid polyp, though rare. Considering the scarcity of more extensive studies on ESS, reporting of cases will aid in formulating management protocols.